THE EFFECT OF TAX FINES, IMPLEMENTATION OF THE SAKPOLE SYSTEM , QUALITY OF FISCAL SERVICES ON TAXPAYER COMPLIANCE AT THE SUKOHARJO SAMSAT OFFICE - Budiyono, Budiyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze Tax Fines, Implementation of the Sakpole System, and the Quality of Tax Service on Taxpayer Compliance. The population in this study were motor vehicle taxpayers registered at the Sukoharjo Samsat Office with an accidental sampling method of 100 people. Based on the Slovin formula, with an error rate of 10%. The analysis techniques in this study consisted of descriptive statistical analysis, instrument testing, classical assumption testing, and hypothesis testing. The results of this study prove the regression results in the regression equation that Tax Fines, Implementation of the Sakpole System, and Quality of Tax Service have a positive effect on Taxpayer Compliance. The results of the F test and t test indicate that Tax Fines, Implementation of the Sakpole System, and Quality of Tax Service have a positive and significant effect on Taxpayer Compliance. Based on the results of the R2 test (coefficient of determination), it is known that Tax Fines, Implementation of the Sakpole System, and Quality of Tax Service are able to explain 49.8% of the variable of Taxpayer Compliance registered at the Sukoharjo Samsat Office , while 50.2% is influenced by other variables that were not studied, such as tax socialization, tax system, tax reform and others . Keywords: Tax Fines, Implementation of the Sakpole System, and Quality of Tax Service, and Taxpayer Compliance .